Substance P Regulation in Epilepsy - Chi, Guangfan; Huang, Zhehao; Li, Xianglan; Zhang, Kun; Li, Guangquan (Current Neuropharmacology, 2018)
Background: Epilepsy is a common neurological disease characterized by abnormal temporary discharge of neurons in the central nervous system. In recent years, studies have revealed the localization and changes in the density of neuropeptides, such as substance P (SP) in the pathogenesis of epilepsy. This review is a concise overview of SP and their physiologic and pathologic functions on regulating epilepsy, and the underline mechanisms. Methods: We research and collect relative online content for reviewing the effects of SP in Epilepsy. Results: The SP/NK-1 receptor system may induce seizures and play an important role in status epilepticus and in experimental animal models of epilepsy. Newest studies show that several mechanisms may explain the excitatory effects of the SP/NK-1 receptor signaling pathway in epilepsy. By binding to the NK-1 receptor, NK-1 receptor antagonists may block the pathophysiological effects of SP, and further studies are needed to confirm the possible anti-epileptic activity of NK-1 receptor antagonists. Conclusion: SP plays crucial roles on through binding with NK-1 receptor during epilepsy pathologic processing, and the NK-1 receptor is receiving a great attention as a therapeutic target for treating epilepsy. Thus, the use of NK-1 receptor antagonists for the treatment of epilepsy should be investigated in further studies.
Keywords: Neuron